A REVISION OF PLETHIANDRA (MBLASTOMATACEAE) - M. P. NAYAR (BRIN Publishing (Penerbit BRIN), 1974)
Seven species are described and a key to the species is presented.The genus is recorded foe the first time from Central Sumatra and this record is an extension of its generic distribution,known previously from Borneo and Malaya. Plethiandra acaminata Merr.and Plethiandra sahebii Burkill are reduced to synonymy and the following new com- binations are proposed: Plethiandra robusta (Cogn.)Nayar,Plethiandra seesiliflora (Cogn.) Merr. var.sessilis (Stapf) Nayar.